Study of mechanical properties of mild steel joint made by electrically assisted friction stir welding using DC and AC. (2021) - Das Chowdhury, Ivy; Sengupta, Kaushik; Singh, Dilip K.; Roy, Swapna; Ghosal, Sujit; Mondal, Arpan Kr; Sengupta, Ujan
Abstract: Hybrid Friction Stir Welding (FSW) has the ability to join high meting point materials, it can also increase the joint efficiency and reduce the tool wear. Generally, in the hybrid FSW, the work pieces to be welded are preheated, post heated or additional heat is provided with some external sources. Different techniques are being studied upon to heat the work pieces. Use of Plasma, Induction, Ultrasonic Vibration, Electric Assistance, etc., are few of the techniques. In the present study, mechanical properties of welded joints using conventional FSW have compared with that of Electrically Assisted Friction Stir Welding (EAFSW) with two different approaches. In the first case, a Direct Current has been used to preheat the carbon steel plates (CS to IS2062 Gr B). In the other case, an alternating current has been used to preheat the plates. The hardness, ultimate tensile strength and weld efficiency of the welded joints were found out for the above-mentioned cases and a comparative study of the mechanical properties have been done. It has been observed that with DC in EAFSW, better joint efficiency has been observed whereas, with AC uniform hardness, in both advancing and retreating side of the joint, has been concluded.